Serum fibroblast growth factor 1 and its association with pancreatic beta cell function and insulin sensitivity in adults with glucose intolerance - Kim, Ji Yoon; Choi, Jimi; Kwon, Yeongkeun; Park, Sungsoo; Kim, Sin Gon; Kim, Nam Hoon (Frontiers in Endocrinology, 2023)
Background: Beneficial role of fibroblast growth factor 1 (FGF1) in the regulation of glucose metabolism and adipose tissue remodeling was suggested in rodents. This study aimed to investigate the association between serum FGF1 levels and metabolic parameters in adults with glucose intolerance. Methods: Serum FGF1 levels were examined using an enzyme-linked immunosorbent assay in 153 individuals with glucose intolerance. Associations between serum FGF1 levels and metabolic parameters, including body mass index (BMI), glycated hemoglobin (HbA1c), and 75 g oral glucose tolerance test-derived parameters, including insulinogenic index (IGI), Matsuda insulin sensitivity index (ISI), and disposition index (DI), were examined. Results: Serum FGF1 was detected in 35 individuals (22.9%), possibly due to the autocrine/paracrine nature of the peptide. IGI and DI levels were significantly lower in individuals with higher FGF1 levels than in those with lower FGF1 levels or undetectable FGF1 (p=0.006 and 0.005 for IGI and DI, respectively, after adjustment for age, sex, and BMI). Univariable and multivariable analyses using the Tobit regression model also revealed a negative association between FGF1 levels and IGI and DI. The regression coefficients per 1-SD of log-transformed IGI and DI were −0.461 (p=0.013) and −0.467 (p=0.012), respectively, after adjustment for age, sex, and BMI. In contrast, serum FGF1 levels were not significantly associated with ISI, BMI, or HbA1c. Conclusions: The serum concentration of FGF1 was significantly elevated in individuals with low insulin secretion, suggesting a possible interaction between FGF1 and beta cell function in humans.